2019
DOI: 10.1080/19415257.2019.1689525
|View full text |Cite
|
Sign up to set email alerts
|

What matters in learning communities for inclusive education: a cross-case analysis

Abstract: Education at the University of Nottingham. She teaches on the face-to-face and online MA courses in Special and Inclusive Education as well as supervising postgraduate research in aspects of inclusive education. She is a member of the forum of the UNESCO Chair for Teacher Education for Diversity and Development and is also a visiting Associate Professor at the Wits School of Education in Johannesburg South Africa. Her research interests include teacher education for inclusive teaching, the knowledge of inclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 39 publications
0
15
0
3
Order By: Relevance
“…In this context, it is useful to entertain Lave and Wenger's (1991) notion of communities of practice because learning in communities can play a central role in teachers' professional development. Promoting an inquiry-based learning in a collaborative reflective approach, can support teacher professional learning (Vangrieken et al 2017;Walton et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is useful to entertain Lave and Wenger's (1991) notion of communities of practice because learning in communities can play a central role in teachers' professional development. Promoting an inquiry-based learning in a collaborative reflective approach, can support teacher professional learning (Vangrieken et al 2017;Walton et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…It is recognised that inclusion and DI will not emerge naturally, but as a result of conscious and reflective actions of schools, communities and teachers (Sandoval, Muñoz, and Márquez 2021). In this sense, it is argued that initial teacher training (Spratt and Florian 2013;Florian and Pantić 2017) and continuous professional development (Florian and Pantić 2017;Vangrieken et al 2017;Walton et al 2022) have an important role to play in how well-prepared new teachers and in-service teachers feel for the challenges of diversity in today's classrooms (European Agency for Development in Special Needs Education 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, within this study, we used one framework of PDIs, the extensive framework of Merchie et al (2018). However, future research could include other features of professional development, for example aspects of learning communities as described by Walton, Carrington, Saggers, Edwards, and Kimani (2019). They concluded that 'if and when learning communities (of whatever variety) emerge or are created to support professional learning for inclusive teaching, there are three factors which can be seen as necessary, though perhaps not sufficient, for their functioning: responsiveness to contextual exigencies, expertise and supportive networks' (p. 13).…”
Section: Discussionmentioning
confidence: 99%
“…This underscored the value and necessity of our use of participatory research approaches such as coteaching (Roth and Tobin 2004) and co-autoethnography with teachers that work within our national system (Wilmes, te Heesen, Siry, Kneip and Heinericy 2018); methodologies that allow us to not only work within the system, and learn about the system, but to also question the system from multiple perspectives. Learning communities operate at the intersections of numerous interacting systems, and recontextualizing learning to unpack difference and work across contextual boundaries can support possibilities for change (Walton et al 2019). It has been through the use of participatory, dialogic, approaches, and the multiple perspectives on CMFs that they afford us in our collaborative research, that we have been able to imagine new possibilities for science instruction in our trilingual national context.…”
Section: Participatory Research Approaches Can Highlight Cmfsmentioning
confidence: 99%